2023
DOI: 10.3390/pathogens12020231
|View full text |Cite
|
Sign up to set email alerts
|

The Bm86 Discovery: A Revolution in the Development of Anti-Tick Vaccines

Abstract: The presence in nature of species with genetic resistance to ticks, or with acquired resistance after repeated tick infestations, has encouraged the scientific community to consider vaccination as an alternative to the unsustainable chemical control of ticks. After numerous attempts to artificially immunize hosts with tick extracts, the purification and characterization of the Bm86 antigen by Willadsen et al. in 1989 constituted a revolutionary step forward in the development of vaccines against ticks. Previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Second, research showed that the phylogeny based on the complete or almost complete sequence of this transcript was in perfect agreement with the recent taxonomy of hard ticks ( 31 , 77 ). This made it an ideal candidate for species identification as it had already demonstrated its utility in representing the genetic diversity of these ticks ( 78 81 ). Furthermore, using this transcript as a marker for species identification would help to better understand the evolution and ecology of these ticks, which are important vectors of various diseases affecting livestock and humans.…”
Section: Discussionmentioning
confidence: 99%
“…Second, research showed that the phylogeny based on the complete or almost complete sequence of this transcript was in perfect agreement with the recent taxonomy of hard ticks ( 31 , 77 ). This made it an ideal candidate for species identification as it had already demonstrated its utility in representing the genetic diversity of these ticks ( 78 81 ). Furthermore, using this transcript as a marker for species identification would help to better understand the evolution and ecology of these ticks, which are important vectors of various diseases affecting livestock and humans.…”
Section: Discussionmentioning
confidence: 99%
“…The cattle tick Rhipicephalus microplus -derived midgut protein Bm86 is currently the only commercialized anti-tick vaccine antigen available [ 1 3 ], but its anti-tick vaccine efficacy varies against different strains and species of ticks from different parts of the world [ 4 ]. This limitation has led several research groups to test novel antigens for anti-tick vaccine development [ 5 ], but only a few antigens have been found to induce adequate immune protection against multiple tick species [ 6 13 ], and some antigens failed to affect the physiological parameters of the tick tested[ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, alternative approaches have been proposed, including pasture rotation, selection of resistant cattle ( Bos indicus ), and biological control using tick-predatory organisms, such as fungi, nematodes, bacteria, and arthropods [ 10 , 11 , 12 , 13 ]; most of these practices are desirable to reduce chemical residues in cattle products and the environment [ 14 ]. On the other hand, immunological control is one of the most important approaches developed since the 1990s and uses the Bm86 antigen, a glycoprotein located at the epithelial cell membrane of the R. microplus tick gut [ 15 , 16 , 17 ]. Commercial tick vaccines have been distributed as TickGARD TM (Australia), GAVAC TM (Latin America), and, more recently, Bovimune Ixovac TM (Mexico).…”
Section: Introductionmentioning
confidence: 99%
“…These patterns also have been observed in the Bm86 protein in Mexican R. microplus strains [ 23 ]. Nevertheless, field trials with Bm86-derived vaccines have been established in Latin America and Australia as an integrated tick management program; the program controlled R. microplus infestations through reduced tick feeding, decreased reproductive capacity and egg lying, and the reduction of larvae in the field in subsequent generations [ 15 , 24 ].…”
Section: Introductionmentioning
confidence: 99%